O conceito de religião em Heidegger: uma possibilidade de superação pela fenomenologia da religião - Schuck, Neivor (2015)
The researchdevelopedin this thesis seeks toHeidegger s concept ofreligioninthe center of the debate about the phenomenology ofreligious life. We seek the possibilityto usethe phenomenologyfounded byHusserlto thinkof the religious experienceandway togive meaning tohuman existence.Our hypothesis come from theidea of unity Heidegger's that want by the ontology shows the search for God distinct of the search of being.Because for the philosopher it is the search for being andfor the philosopher of religion it s the search for reasons to postulate God. This theme appears due the criticism ofHeidegger about thetraditional theology, and in specialthe peripheraltheologiesasthe theology ofliberationthat confusedthe sacred with the political. ForHeideggerthe artist andthe posture the ones walking closer in the search of God, and reveal it in their work